## Converting between natural logarithms and exponential functions

Start with a general natural logarithm: \(\ln(x) = y\). You can easily rewrite this as \(\log_e(x) = y\).

As always, you need to label each part of the function: the base is *e* (as with natural logarithms), the exponent is *y*, and the answer of the exponential is *x.*

Therefore you can rewrite logarithms as \(e^y = x\).

Solve \(e^x = 5\) to 3 sf

- Label each part of the function so: the base is e, the exponent is x, and the answer of the exponential is 5.
- Then formulate it into a logarithm to become \(\log_e(5) = x\)
- As Log
_{e}is the same as saying Ln, you can write it as a natural logarithm

## What are the rules for natural logarithms?

Along with the specific rules for natural logarithms, you can use the general Laws of Logs as well as the Exponential Rules.

### Rules for natural logarithms

- \(\ln(e) = 1\)
- \(\ln(1) = 0\)
- \(\ln(e^x) = x\)
- If \(\ln(y) = \ln(x)\), then y = x
- \(e^{\ln(x)} = x\)

## Proving natural logarithm rules

Just like the proofs for Laws of Logs, you need to be able to understand each step of proving a natural logarithm rule – you do not need to feel like you could have got to that point without any help.

### Proving Ln (1) = 0

\(\ln(1) = m\) can be written as \(\log_e(1) = m\)

You will rewrite it as an exponential function where the base is e, the answer of the exponential is 1, and the exponent is m. This exponential would look like this: \(e^m = 1\)

Using our Power = 0 exponential law, you know that the exponent (in this case, m) must be 0 for the answer to the exponential to be 1.

Thus \(\ln(1) = 0\)

### Proving Ln (e) = 1

\(\ln(e) = n\) can be rewritten as \(\log_e(e) = n\) where the base is e, the answer to the exponential is e, and the exponent is n.

As a result, you rewrite \(\log_e(e) = n\) as \(e^n = e\).

According to our exponential rules, when the answer to the exponential is the same as the base, then the power must be 1.

Thus, \(\ln(e) = 1\)

### Proving Ln(e^{x})=x

As exponential and logarithms are inverse functions, they cancel each other out when they are placed in the same function.

This concept is the same as multiplying a number by 2 and then dividing by 2 – you end up with the same number you have in the beginning.

Therefore, ln and e will cancel out so that you are left with just x.

### Proving Ln (y) = Ln (x) means y = x

If you set ln(y) = a and ln(x) = b, you can rewrite each function as an exponential.

- \(\ln(y) = a, \log_e(y) = a\)

Where the base is e, the exponent is a, and answer to the exponential is y. Therefore, the exponential is \(e^a = y\).

- \(\ln(x) = b, \log_e(x) = b\)

Where the base is e, the exponent is b, and the answer to the exponential is x. Therefore, the exponential is \(e^b = x\).

Because you are told ln (y) = ln (x), \(e^a\) must be equal to \(e^b\), therefore y = x.

### Proving e^{Ln(x)}=x

The e and the Ln cancel each other out because exponentials and logarithms are the inverse functions of each other. By doing so, you are left with x.

Therefore, \(e^{\ln(x)} = x\)

This law uses the same thinking as the \(\ln(e^x) = x\)

## Application of natural logarithm rules

**Example 1: **Solve** \(e^{2x} = 6\)**

The expression \(e^{2x} = 6\) can be written as a natural logarithm as the base is e, the exponent is 2x, and the answer to the exponential is 6.

** **

So as a natural logarithm, it could be written as ln (6) = 2x.

Therefore, \(\frac{\ln(6)}{2} = 0.896 (3 s.f)\)

**Example 2: **Solve \(e^{x+3} = 10\)

The expression \(e^{x+3}\) can be written as a logarithm, whereby the base is *e*; the exponent is x + 3, and the answer to the exponential is 10.

\(\ln(10) = x + 3\)

Therefore, \(x = \ln(10) - 3 = -0.697(3 s.f)\)

**Example 3: **Solve \(e^{\ln(x^3)} = 8\)

As the exponential and logarithms are inverse functions, the *e* and Ln will cancel each other.

Therefore, \(x^3 = 8; x = 2\)

**Example 4: **Solve \(\ln(x+1) = 1.4\)

To get x on its own, we need to convert the logarithm to an exponential where the base is e, the exponent is 1.4, and the answer to the exponential is x + 1.

Therefore, \(e^{1.4} = x+1\) and \(x = e^{1.4} -1 = 3.06(3 s.f)\)

**Example 5: **Solve \(2\ln(6) + \ln(2) - \ln(4) = x\)

1. Due to the power logarithm rule, \(2\ln(6)\) can be written as \(\ln(6^2) = \ln(36)\)

Therefore, \(\ln(36) +\ln(2) - \ln(4) = x\)

2. Using the product and quotient rule, we can do this further:

\(\ln(36 \cdot 2) - \ln(4) = x\)

\(\ln(\frac{36 \cdot 2}{4}) = x\)

\(\ln(\frac{72}{4}) = \ln(18) = x = 2.89 (3 s.f)\)

## Natural Logarithm - Key takeaways

- Natural logarithms are logarithms with the base of
*e.* - To use natural logarithms to solve and simplify, you can use:\(\ln(1) = 0\); \(\ln(e) = 1\); if \(\ln(y) = \ln(x)\), then y = x; \(e^{\ln(x)} = x\). This is alongside the laws for both Exponentials and Logarithms.

###### Learn with 17 Natural Logarithm flashcards in the free StudySmarter app

We have **14,000 flashcards** about Dynamic Landscapes.

Already have an account? Log in

##### Frequently Asked Questions about Natural Logarithm

What is a natural logarithm?

Natural logarithms are logarithms with the base of e.

Why do we use natural logarithms?

We can use natural logarithms to solve functions with a base of e.

What is a natural logarithm example?

Natural logarithms are denoted using Ln (x).

How do we expand a natural logarithm?

To expand a logarithm is to break down a single logarithm to its individual parts. We can do this with natural logarithms using the rules for natural logarithms as well as the rules for general logarithms and exponentials.

##### About StudySmarter

StudySmarter is a globally recognized educational technology company, offering a holistic learning platform designed for students of all ages and educational levels. Our platform provides learning support for a wide range of subjects, including STEM, Social Sciences, and Languages and also helps students to successfully master various tests and exams worldwide, such as GCSE, A Level, SAT, ACT, Abitur, and more. We offer an extensive library of learning materials, including interactive flashcards, comprehensive textbook solutions, and detailed explanations. The cutting-edge technology and tools we provide help students create their own learning materials. StudySmarter’s content is not only expert-verified but also regularly updated to ensure accuracy and relevance.

Learn more